Estetika Kolaborasi Musik Tradisi–Modern: Studi Kasus Komposisi Peucang oleh SORA - Reffali, Soni; Yully Hidayah; Etti Suharti (LP2M ISBI Bandung, 2025)
This article explores the aesthetic dynamics of collaboration between traditional and modern musical elements through a case study of Peucang, a composition by the music collective SORA (Sound of Heritage). The study focuses on how the integration of traditional Sundanese musical idioms with contemporary composition techniques produces a new musical expression rooted in local identity while being open to global sensibilities. The research employs an analytical-descriptive method by examining structural, thematic, and textural aspects of the composition. The findings reveal that Peucang embodies a dialogic approach, where traditional and modern elements are not juxtaposed superficially but interwoven into a cohesive musical language. This collaborative model demonstrates a pathway for sustainable cultural innovation, where tradition is not merely preserved but transformed and revitalized through creative reinterpretation. The article contributes to ongoing discourses on musical hybridity, cultural continuity, and the role of aesthetic agency in contemporary composition practices.